Rural tourism: Activities and challenges - Muhammad Ramli; Hasan Basri; Muhammad Adi Junaidi; Irwan Rahadi; Muh Hilmi Pauzi (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Rural tourism is perceived to develop the tourism niche segment to reduce the influence of mass tourism. To prevent the risk of natural damage, rural tourism comes as a solution to improve the economy of rural areas and provide education, mixed experiences and offers high levels of service. This study aims to explain the activities of rural tourism that have been determined by the tourism office and the challenges of their development. The ethnographic method is used to cluster activities and problems related to tourism activities in the Rural Tourism area in Lombok Timur. This type of research adopts a case study covering three zones; marine zoning, mountain range zoning, and natural zoning (flat landscape). The sampling technique used was random clustering sampling by selecting three representatives from each sample cluster. The reasons supporting the selection of this sample model are assumed that all samples have the same characteristics. The data collection process was carried out by participant observation, document review, semi-structured interviews, and field notes. All representational tourism activities and development barriers in rural (Desa Wisata) areas are discussed.